Regional regulation of Filiform tongue papillae development by Ikkα/Irf6. Issue 9 (13th July 2016) - Kawasaki, Maiko; Kawasaki, Katsushige; Oommen, Shelly; Blackburn, James; Watanabe, Momoko; Nagai, Takahiro; Kitamura, Atsushi; Maeda, Takeyasu; Liu, Bigang; Schmidt‐Ullrich, Ruth; Akiyama, Taishin; Inoue, Jun‐Ichiro; et al.
Abstract : Background : Non‐gustatory filiform papillae play critical roles in helping to grip food, drawing food to the esophagus, cleaning the mouth, and spreading saliva. The molecular mechanisms of filiform tongue papillae development however are not fully understood.Results : We found Ikkα and Irf6 expression in developing tongue epithelium, and describe here specific tongue abnormalities in mice with mutation of these genes, indicating a role for Ikkα and Irf6 in filiform papillae development. Ikkα and Irf6 mutant tongues showed ectopic vertical epithelium at the midline, while lateral sides of mutant tongues adhered to the oral mucosa. Both the ectopic median vertical epithelium and adhered epithelium exhibited the presence of filiform tongue papillae, whereas epithelium between the median vertical epithelium and adhered tongue showed a loss of filiform tongue papillae. Timing of filiform papillae development was found to be slightly different between the midline and lateral regions of the wild‐type tongue.Conclusions : Filiform papillae thus develop through distinct molecular mechanisms between the regions of tongue dorsum in the medio‐lateral axis, with some filiform papillae developing under the control of Ikkα and Irf6 . Developmental Dynamics 245:937–946, 2016 . © 2016 Wiley Periodicals, Inc.